Synthesis of Cinnamoylhydroxamic Acid Derivatives Bearing Sulfonamide, Amide Bonds as Connecting Unit Targeting Histone Deacetylases - Quoc, Nguyen Cuong; Quang, Le Dang; Tuan, Nguyen Duy; Khang, Tran Duy; Linh, Nguyen Vu; Men, Tran Thanh; Tuan, Nguyen Trong; Hue, Bui Thi Buu; De, Tran Quang (VNU Journal of Science: Natural Sciences and Technology; Vol 40 No 1, 2024)
Based on the strong activity of belinostat, the study synthesized of some cinnamoylhydroxamic acid derivatives with the aim of creating new compounds that have the potential to selectively inhibit HDAC to contribute to cancer treatment.  N -hydroxycinnamamide serves as both ZBG and the linker group. The derivatives orient to the HDAC2 and HDAC8 enzymes by molecular docking. Compound 9a (bearing sulfonamide) exhibited as the most potential candidate to inhibit the function of HDAC2 enzyme.